Westonci.ca makes finding answers easy, with a community of experts ready to provide you with the information you seek. Discover solutions to your questions from experienced professionals across multiple fields on our comprehensive Q&A platform. Discover detailed answers to your questions from a wide network of experts on our comprehensive Q&A platform.

3. Given that [tex]r=\binom{4a}{3}, q=\binom{5}{-4}[/tex] and [tex]r \cdot q=-2[/tex], find the value of [tex]a[/tex].

4. Two vectors [tex]y[/tex] and [tex]z[/tex] are given by [tex]\binom{3-x}{5x-2}[/tex] and [tex]\binom{-1}{-1}[/tex] respectively. If [tex]y \cdot z=-9[/tex], find the value of [tex]x[/tex].


Sagot :

Let's solve the given problems step-by-step:

### Problem 3:
Given that [tex]\( r = \binom{4a}{3} \)[/tex], [tex]\( q = \binom{5}{-4} \)[/tex], and [tex]\( r \cdot q = -2 \)[/tex], we need to find the value of [tex]\( a \)[/tex].

1. Understanding the Binomial Coefficient [tex]\( q \)[/tex]:
[tex]\[ q = \binom{5}{-4} \][/tex]
The binomial coefficient [tex]\( \binom{n}{k} \)[/tex] is defined for non-negative integers [tex]\( n \)[/tex] and [tex]\( k \)[/tex]. If [tex]\( k \)[/tex] is negative, the binomial coefficient is zero:
[tex]\[ \binom{5}{-4} = 0 \][/tex]

2. Analyzing the Given Equation:
Since [tex]\( q = 0 \)[/tex], we substitute [tex]\( q \)[/tex] into [tex]\( r \cdot q \)[/tex]:
[tex]\[ r \cdot q = r \cdot 0 = 0 \][/tex]
However, it is given that [tex]\( r \cdot q = -2 \)[/tex]. This leads to a contradiction because any number multiplied by zero should result in zero, not [tex]\(-2\)[/tex]. Therefore, there seems to be an inconsistency in the problem as stated, and it cannot be solved with the given information.

### Problem 4:
Given two vectors:
[tex]\[ y = \begin{pmatrix} 3 - x \\ 5x - 2 \end{pmatrix}, \quad z = \begin{pmatrix} -1 \\ -1 \end{pmatrix} \][/tex]
we need to find the value of [tex]\( x \)[/tex] such that the dot product [tex]\( y \cdot z = -9 \)[/tex].

1. Compute the Dot Product:
The dot product of two vectors [tex]\( y \)[/tex] and [tex]\( z \)[/tex] is given by:
[tex]\[ y \cdot z = (3 - x)(-1) + (5x - 2)(-1) \][/tex]

2. Expand and Simplify:
[tex]\[ y \cdot z = - (3 - x) - (5x - 2) \][/tex]
[tex]\[ y \cdot z = -3 + x - 5x + 2 \][/tex]
[tex]\[ y \cdot z = -3 + 2 + x - 5x \][/tex]
[tex]\[ y \cdot z = -1 - 4x \][/tex]

3. Set Equal to the Given Value:
Given [tex]\( y \cdot z = -9 \)[/tex], we substitute and solve for [tex]\( x \)[/tex]:
[tex]\[ -1 - 4x = -9 \][/tex]
[tex]\[ -1 - 4x + 1 = -9 + 1 \][/tex]
[tex]\[ -4x = -8 \][/tex]
[tex]\[ x = 2 \][/tex]

So, the value of [tex]\( x \)[/tex] is [tex]\(\boxed{2}\)[/tex].

### Final Answers:
3. The value of [tex]\( a \)[/tex] cannot be determined due to an inconsistency in the provided information.
4. The value of [tex]\( x \)[/tex] is [tex]\(\boxed{2}\)[/tex].
We appreciate your time. Please revisit us for more reliable answers to any questions you may have. We hope you found this helpful. Feel free to come back anytime for more accurate answers and updated information. We're glad you chose Westonci.ca. Revisit us for updated answers from our knowledgeable team.